DEVELOPMENT OF INTERACTIVE E-LKPD BASED ON THE R2L METHOD TO IMPROVE STUDENTS’ HOTS SCIENCE LITERACY - Silvia Gressiela Br Sembiring; Iis Siti Jahro (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research aims to find out data and information about students' needs of Interactive e-LKPD based on the Reading to Learn (R2L) method to improve Students’ HOTS Science Literacy on Reaction Rates; to find out data and information on the level of interactive feasibility of E-LKPD developed; to determine the influence of the interactive implementation of E-LKPD; to determine the level of effectiveness of interactive E-LKPD. This investigation employs a 4D model methodology. Based on questionnaire results 88.2% students’ needs to E-LKPD based on R2L Method. Based on four material expert validators, it was determined that 4.32 of the material had a very valid or feasible, while 87.40% of student responses were rated as "very interesting." There is an influence in the use of E-LKPD with R2L method with a significance result of 0.000 <0.05. The level of effectiveness of E-LKPD is classified at the medium level with the N-Gain results obtained of 0.48. From these results it is concluded that the E-LKPD based on R2L Method can increase students' HOTS Science Literacy in the medium category. Keywords: E-LKPD, HOTS, Reaction Rates. Reading to Learn, Science Literacy Abstrak: Penelitian ini bertujuan untuk mengetahui data dan informasi tentang kebutuhan siswa terhadap e-LKPD Interaktif berbasis metode Reading to Learn (R2L) untuk meningkatkan Literasi HOTS IPA Siswa pada materi Laju Reaksi; mengetahui data dan informasi tentang tingkat kelayakan interaktif E-LKPD yang dikembangkan; mengetahui pengaruh penerapan interaktif E-LKPD; mengetahui tingkat efektivitas E-LKPD interaktif. Penelitian ini menggunakan metodologi model 4D. Berdasarkan hasil angket, 88,2% kebutuhan siswa terhadap E-LKPD berbasis Metode R2L terpenuhi. Berdasarkan empat validator ahli materi, ditetapkan bahwa 4,32 materi memiliki nilai sangat valid atau layak, sedangkan 87,40% respon siswa dinilai "sangat menarik". Terdapat pengaruh dalam penggunaan E-LKPD dengan metode R2L dengan hasil signifikansi 0,000 < 0,05. Tingkat efektivitas E-LKPD tergolong sedang dengan hasil N-Gain yang diperoleh sebesar 0,48. Dari hasil tersebut dapat disimpulkan bahwa E-LKPD berbasis Metode R2L dapat meningkatkan Literasi IPA HOTS siswa pada kategori sedang. Kata Kunci: E-LKPD, HOTS, Laju Reaksi, Membaca untuk Belajar, Literasi IPA